Integrasi Nilai Inklusivitas dan Kesetaraan Gender dalam Pembelajaran Matematika SMP: Strategi, Implementasi, dan Asesmen - Yulia Isnaeni; Salma Farah Nabillah; Nina Kartina; Dr. Rosynanda Nur Fauziah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics education at the junior high school level plays an important role in building critical thinking, creativity, communication, and collaboration skills in the 21st century era. Although mathematical abilities between genders tend to be equal, students' learning experiences in Indonesia are still influenced by social stereotypes, limitations of adaptive teaching media, and potentially biased assessment designs. This article aims to map and develop a framework for mathematics learning strategies that support inclusivity and gender equality in the context of teacher innovation in the Independent Curriculum. The research uses a systematic literature review approach with thematic-narrative synthesis. The literature was collected from international and national scientific databases, selected in stages using the full text identification–screening–feasibility flow, and reviewed for quality through a methodological checklist from the Joanna Briggs Institute. Data were analyzed through open and axial coding to produce key themes including differentiation (content-process-product), heterogeneous collaborative learning with non-gender role rotation, use of neutral context in the questions, and adaptive authentic assessment design that assesses thought processes and group contributions. Key findings confirm that gender inclusion and equity in mathematics are determined more by the structure of application and design of learning experiences than by differences in basic abilities. Practically, this article offers a contribution in the form of a prototype teacher toolkit that includes a checklist of bias-free materials and questions (aspects of language, context, role, and name representation), operational examples of SPLDV differentiation tasks (visual–numeric–verbal), as well as a 4C-based assessment rubric model and equality reflection. The implication is that teachers can directly use adaptive OER and bias check instruments in module planning, while schools and policy makers such as BSKAP and the Ministry of Primary and Secondary Education of the Republic of Indonesia can strengthen support through micro-training, practitioner communities, and improvement of the assessment ecosystem in education units.